Fluency Problems Faced by Students While Speaking English as a Second Language: A Case Study of Undergraduate Students of Department of English in the University of Larkano - Ali Zaman Kalhoro*; Khalil Jibran Abbasi; Wazir Ali Tunio; Muhammad Yaseen (Social Science Review Archives, 2025)
The reason behind conducting this research is to inspect the core problem of fluency in English faced by university students of final year class belonging to English Language and Literature Department at The University of Larkano. Fluency in English is a crucial skill for undergraduate students, particularly those who are in English Department. However, many second-language learners struggle with fluency due to language problem, limited speaking practice, and hesitation barriers such as anxiety and lack of confidence. This study investigates the fluency challenges faced by undergraduate students at the University of Larkano, examining the factors that hinder their ability to communicate effectively in English. Through a semi-structured interview approach, data was collected from sixteen students, highlighting common problems such as limited classroom interaction, insufficient institutional support, and fear of making mistakes. Findings suggest that students require more structured speaking activities, interactive learning environments, and greater encouragement from instructors to improve their fluency. Because the mostly the course of conduct at the university is English Literature and Linguistic is counted as a minor Hence the recommendations are interactive discussions, speaking environments, and real-life communication tasks which help students overcome fluency-related problems.